2021
DOI: 10.3389/fonc.2021.690422
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Intra-Fraction Prostate Motion During Stereotactic Irradiation in First Irradiation and Re-Irradiation

Abstract: BackgroundUnderstanding intra-fractional prostate motions is crucial for stereotactic body radiation therapy (SBRT). No studies have focused on the intra-fractional prostate motions during re-irradiation with SBRT. The objective was to evaluate these translational and rotational motions in primary treated patients and in the context of re-irradiation.MethodsFrom January 2011 to March 2020, 162 patients with histologically proven prostate cancer underwent prostate SBRT, including 58 as part of a re-irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The simulated percent of time within thresholds per patient shown in Figures 5 and 6 considering the vector extremes of a 'worst case' displacement for the imaging interval indicated that when aggregating motion per patient the mean percent of time patients CTV within 3 mm 96.2% (1. 7 in agreement with this finding [12]. Furthermore Curtis et al, also reports that the analysis was completed under the assumption that a perfect correction occurred immediately for each interval simulated from the real-time data and as such, their analysis estimates an upper bound of the gain possible from frequent repositioning whereas the methods used in the current study are likely to have more conservative results.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The simulated percent of time within thresholds per patient shown in Figures 5 and 6 considering the vector extremes of a 'worst case' displacement for the imaging interval indicated that when aggregating motion per patient the mean percent of time patients CTV within 3 mm 96.2% (1. 7 in agreement with this finding [12]. Furthermore Curtis et al, also reports that the analysis was completed under the assumption that a perfect correction occurred immediately for each interval simulated from the real-time data and as such, their analysis estimates an upper bound of the gain possible from frequent repositioning whereas the methods used in the current study are likely to have more conservative results.…”
Section: Discussionsupporting
confidence: 77%
“…Kioke et al, analysed 16 patients treated with CyberKnife and reported an a mean and standard deviation (SD) of 0.03 (0.91), -0.01 (0.35) and -0.02 (1.04) mm with average imaging interval of 70 seconds taken as the total treatment time divided by the total number of acquired images [11]. Taillez et al, calculated translations and rotations from 162 patients treated wit CyberKnife in order to observe the changes in deviations over the length of the treatment [12].…”
Section: Introductionmentioning
confidence: 99%
“…These treatments times are much shorter than CyberKnife treatments and multiple studies have shown that the longer the treatment time, the larger magnitude motion shifts, 25,26 although studies have noted a plateau in motion magnitude after approximately 20 min. 27 In this study imaging intervals were relatively short when compared to the imaging intervals of previous CyberKnife studies. It has been shown that rapid prostate motions can occur, so the authors believe these shorter imaging intervals are warranted to allow for treatment to be halted after large shifts have occurred.…”
Section: Discussionmentioning
confidence: 86%
“…These treatments times are much shorter than CyberKnife treatments and multiple studies have shown that the longer the treatment time, the larger magnitude motion shifts, 25 , 26 although studies have noted a plateau in motion magnitude after approximately 20 min. 27 …”
Section: Discussionmentioning
confidence: 99%
“…According to the aforementioned latest systematic review of the literature [31], 18 articles are available in the current literature concerning salvage prostate Re-I, accounting for a total of 511 patients with a median follow-up of 22 months (range 9.6-77.6). However, more recent articles have been published in the last 2 years [60][61][62][63][64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%